2010
DOI: 10.1590/s0102-05362010000100007
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade de alface e rúcula, em sistema consorciado, sob adubação orgânica e mineral

Abstract: A s atuais mudanças na política global, com diretrizes ecológicas, a crescente demanda por produtos orgâ-nicos no mundo e as restrições impostas pelos países importadores quanto à qualidade e à segurança alimentar têm gerado a necessidade de estudos e técnicas alternativas para a produção de frutos e hortaliças que minimizem a utilização de adubos minerais ou agroquímicos (Fontanétti et al., 2004).Com o aumento da modernização OLIVEIRA EQ; SOUZA RJ; CRUZ MCM; MARQUES VB; FRANÇA AC. 2010. Produtividade de alfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
2
35

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 6 publications
5
19
2
35
Order By: Relevance
“…Com esta prática, busca-se maior produção por área pela combinação de plantas que irão utilizar espaço, nutrientes e luz solar, além dos benefícios que uma planta traz para a outra no controle de plantas concorrentes, pragas e doenças (PIVETTA, et al, 2007;SILVA et al, 2011). Entre as espécies olerícolas que se pode combinar com vantagens agroeconômicas e ambientais estão a alface e rúcula (COSTA et al, 2007;OLIVEIRA et al, 2010). Elas têm elevado valor nutricional, são bastante usadas na alimentação humana e contribuem primariamente com vitaminas e sais minerais.…”
Section: Introductionunclassified
“…Com esta prática, busca-se maior produção por área pela combinação de plantas que irão utilizar espaço, nutrientes e luz solar, além dos benefícios que uma planta traz para a outra no controle de plantas concorrentes, pragas e doenças (PIVETTA, et al, 2007;SILVA et al, 2011). Entre as espécies olerícolas que se pode combinar com vantagens agroeconômicas e ambientais estão a alface e rúcula (COSTA et al, 2007;OLIVEIRA et al, 2010). Elas têm elevado valor nutricional, são bastante usadas na alimentação humana e contribuem primariamente com vitaminas e sais minerais.…”
Section: Introductionunclassified
“…Abreu et al (2010), Oliveira et al (2010), and Resende et al (2010) observed that the production of lettuce, lettuce, and rocket and onion, respectively, was improved using the organic system. In contrast, Carvalho et al (2013), Menezes Júnior et al (2014, and Santos et al (2015) observed that the conventional system was superior to the organic system regarding the increase in carrot, onion, and green corn production, respectively.…”
mentioning
confidence: 99%
“…Bulb diameter according to the types of fertilization: control -A0, earthworm humus -A1, earthworm humus + NPK -A2 (5A) and nitrogen doses: 0, 0.7, 1.4, 2.1 and 2.8 g pot -1 (5B) of the beet at 45 days after transplanting Bulb fresh weight and bulb dry weight as a function of the basal fertilization showed better performance in the fertilizations with earthworm humus and earthworm humus + NPK, compared with the control, which contained only the nutrients present in the soil analysis ( Figures 6A and 6B). Oliveira et al (2010) report in their studies that organic fertilization and associated with mineral fertilization positively influence the yield of the crops, since the nutrients are not easily lost by leaching or volatilization. Damasceno et al (2011), studying beet yield as a function of N doses, observed that as the N dose increased there was an increment in bulb fresh phytomass.…”
Section: Resultsmentioning
confidence: 99%